Pengaruh Ukuran Perusahaan, Informasi Laba, Kebijakan Dividen Dan Leverage Terhadap Abnormal Return - Felicia, Susanto Salim (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study aims to determine and analyze the influence of company size, earnings information, dividend policy and leverage on abnormal returns. Data analysis method used is classical assumption analysis, descriptive statistical test, f test, t test and test coefficient of determination. Testing the hypothesis in this study uses the t test. The results of the study show that firm size and leverage have no significant effect on abnormal returns, while earnings information has a significant positive effect on abnormal returns and dividend policy has a significant negative effect on abnormal returns.